Analysis of The Figurative Language in The Novel Pergi by Tere Liye - Pardi, Pardi; Hariani, Safitri; Asnani, Asnani; Pratiwy, Devi; Mardiansyah, Mardiansyah (International Journal of English and Applied Linguistics (IJEAL), 2025)
This study examines the use of figurative language in the novel Pergi by Tere Liye published by Republika Penerbit on April in 2018, focusing on personification, metaphor, simile, and hyperbole. In this study the author refers to the theory of Gorys Keraf (2010). The research aims to identify the types of figurative language used, analyse their meanings, and reveal the implicit messages conveyed by the author. The method used is qualitative descriptive analysis, with data collection techniques involving in-depth reading and classification of sentences containing specific figurative language elements. The findings indicate that Tere Liye predominantly uses personification and metaphor to depict the emotions and situations faced by the main character, while similes and hyperboles are utilized to enhance the dramatic effect of the narrative. These stylistic devices not only enrich the novel's aesthetics but also play a crucial role in conveying moral messages and life values to the readers.